Intrauterine therapy for macrocystic congenital cystic adenomatoid malformation of the lung - Min, Jin-Young (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology; Korean Urogynecologic Society, 2014)
OBJECTIVE: To report on our experiences with thoracoamniotic shunting and/or the injection of a sclerosing agent (OK-432) to treat fetuses diagnosed with macrocystic congenital cystic adenomatoid malformation (CCAM) of the lung. METHODS: A retrospective study was undertaken in six fetuses with macrocystic CCAM at our institute that had been confirmed by postnatal surgery between August 1999 and January 2012. RESULTS: Six fetuses that had been diagnosed with macrocystic CCAM were analyzed. The median gestational age at diagnosis was 23.5 weeks (range, 19.5-31.0 weeks), and at the time of primary treatment was 24.0 weeks (range, 20.5-31.0 weeks). The mean size of the largest cyst at the initial assessment was 42.5±15 mm. Four fetuses were associated with mediastinal shifting, and one also showed fetal hydrops. All fetuses underwent a shunting procedure within the cysts, one case among them was also treated with OK-432. After the completion of all procedures, the mean size of the largest cyst was all decreased (14.2±12 mm). The median gestational age at delivery was 38.0 weeks (range, 32.4-40.3 weeks). All of the newborns underwent the surgical resection at a median age of 6 days (range, 1-136 days) and are currently doing well without any complications. CONCLUSION: We suggest that intrauterine decompression therapy to manage fetal macrocystic CCAM is recommendable treatment for good perinatal outcome.